Vaginismus as a Genito-Pelvic Pain/Penetration Disorder (GPPPD): Etiology, Pathophysiology, Diagnosis, and Multimodal Therapeutic Approach - Imam Irawan Saputra Hasibuan; Teuku Yudhi Iqbal (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Vaginismus is a sexual dysfunction disorder in women characterized by the inability or difficulty to achieve penetration due to involuntary contraction of the pelvic floor muscles, often accompanied by pain as well as anxiety and avoidance responses. In the latest classification, this condition is included in genito-pelvic pain/penetration disorder (GPPPD). The prevalence of vaginismus varies and tends to be underdiagnosed due to stigma, embarrassment, and limitations in reporting and clinical examination. The etiology of vaginismus is multifactorial, involving the interaction of biological, psychological, and sociocultural factors. Its pathophysiology is related to a recurring pain–fear–muscle contraction cycle, which exacerbates symptoms and perpetuates the disorder. Diagnosis is established through targeted history taking, assessment of pain and anxiety related to penetration, and evaluation of the patient’s response to gradual examination. Management is carried out using a multimodal and stepwise approach, including education, progressive dilator therapy, pelvic floor physiotherapy, and psychological interventions such as sexual counseling and cognitive behavioral therapy. In severe or refractory cases, additional therapies such as botulinum toxin may be considered. A comprehensive and integrated approach is expected to improve treatment outcomes and patients’ quality of life.